2006
DOI: 10.1007/s11481-006-9040-4
|View full text |Cite
|
Sign up to set email alerts
|

WIN55,212-2-Mediated Inhibition of HIV-1 Expression in Microglial Cells: Involvement of Cannabinoid Receptors

Abstract: Cannabinoid receptors CB(1) and CB(2) are primarily expressed in cells of the nervous and immune systems, respectively. Recently, the synthetic CB(1)/CB(2) agonist WIN55,212-2 was found to suppress replication of HIV-1 in microglial cell cultures. The present study was undertaken to test the hypothesis that WIN55,212-2's antiviral effect is mediated via CB(2) receptors. By reverse transcription-polymerase chain reaction, microglia were found to express both CB(1) and CB(2) receptors. Using additional CB(1)/CB(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
0
43
1
Order By: Relevance
“…Esposito et al (2002) reported that activation of the CB 1 receptor protects rat glioma cells from nitric oxide-mediated cell toxicity induced by the Tat protein. Rock et al (2007) showed that the CB 2 receptor is involved in cannabinoid-mediated inhibition of viral replication in microglial cell cultures and that cannabinoids down-regulate the HIV-1 coreceptor CCR5. Cannabinoid agonists also have been reported to significantly decrease the permeability of human brain microvascular endothelial cells induced by the HIV-1 envelope glycoprotein Gp120 by preventing the down-regulation of the tight junction proteins, claudin-5 and zonula occludens-1 (Lu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esposito et al (2002) reported that activation of the CB 1 receptor protects rat glioma cells from nitric oxide-mediated cell toxicity induced by the Tat protein. Rock et al (2007) showed that the CB 2 receptor is involved in cannabinoid-mediated inhibition of viral replication in microglial cell cultures and that cannabinoids down-regulate the HIV-1 coreceptor CCR5. Cannabinoid agonists also have been reported to significantly decrease the permeability of human brain microvascular endothelial cells induced by the HIV-1 envelope glycoprotein Gp120 by preventing the down-regulation of the tight junction proteins, claudin-5 and zonula occludens-1 (Lu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that cannabinoids inhibit viral expression and downregulate CC chemokine receptor 5 (CCR5), a chemokine receptor that is a coreceptor for HIV-1 entry (Rock et al, 2007). In addition, cannabinoid receptor agonists have been reported to decrease significantly the permeability of human brain microvascular endothelial cells induced by Gp120 by preventing the down-regulation of integral tight junction proteins (Lu et al, 2008).…”
mentioning
confidence: 99%
“…Cannabinoids may also modulate the activity of TRPV1, TRPA1, and TRPM8 channels by a yet unknown mechanism (196). Rodent microglial cells in vitro express CB 1 and CB 2 cannabinoid receptors as well as the third, not yet cloned, receptor (114,259,744,766). The constitutive expression of cannabinoid receptors in the resting microglia is very low, if at all existing.…”
Section: E Cannabinoid Receptorsmentioning
confidence: 99%
“…Glial cells involved in mediating inflammatory processes are resident within the spinal cord and include both astroglia and microglia, the latter of which has been directly implicated in the initiation of peripheral injury-induced pain [12]. Moreover, microglia have been shown to express cannabinoid receptors [13][14][15][16], and to produce and inactivate endocannabinoids [15,17,18].…”
Section: Introductionmentioning
confidence: 99%